Pembuatan Ecobrick sebagai Upaya Pengelolaan Sampah Plastik dan Pelestarian Lingkungan di Kelurahan Tanjung Uban Selatan, Kecamatan Bintan Utara, Kabupaten Bintan, Provinsi Kepulauan Riau - Beizil Hakimi; Adinda Adinda; Andrean Bayu Pratama; Apriliani Putri; Dela Afrilia; E. Refal Driyatama Putra; Fera Mardiani; Jelaine Yuli Nesia Sinaga; Natasya Cahya Anjani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Plastic waste continues to be one of the most pressing environmental problems due to its persistence, excessive use in daily life, and difficulty in decomposition. In many communities, including Tanjung Uban Selatan Village, unmanaged plastic waste accumulates in the environment, contributing to pollution and health risks. This community service activity aims to introduce and implement ecobricks as a simple yet effective solution to manage plastic waste. Ecobricks are not designed to destroy plastic but to recycle and repurpose it into useful and even marketable products. The process of making ecobricks requires no special expertise or significant costs, as the primary material is household plastic waste. The activity involved socialization, practical workshops, and guidance for residents on how to properly produce ecobricks. Results from the program show that residents were able to collect and process previously unmanaged plastic waste into solid, reusable building blocks. These ecobricks have potential applications for creating furniture, decorative items, and even small-scale construction, thereby providing both environmental and economic value. Beyond reducing plastic waste, the initiative also fosters community awareness about sustainable waste management practices and promotes environmental responsibility. In conclusion, the introduction of ecobricks in Tanjung Uban Selatan Village demonstrates that simple innovations can empower communities to transform environmental challenges into opportunities for sustainability and income generation.